To solve the equation x^2 -4x -3=0 using the quadratic formula, we first identify the coefficients of the equation: a = 1, b = -4, and c = -3.
The quadratic formula is given by:
x = (-b ± √(b^2 - 4ac))/(2a)
Substituting the values of a, b, and c into the formula, we have:
x = (-(-4) ± √((-4)^2 - 4(1)(-3)))/(2(1))
x = (4 ± √(16 + 12))/(2)
x = (4 ± √28)/2
x = (4 ± 2√7)/2
Now we simplify the expression:
x = 2 ± √7
So the solutions to the equation x^2 -4x -3=0 are x = 2 + √7 and x = 2 - √7.
Note: Enter your answer and show all the steps that you use to solve this problem in the space provided. Use the quadratic formula to solve the equation x^2 -4x -3=0
1 answer